PENINGKATAN KETERAMPILAN MENULIS MENGGUNAKAN MODEL SCAFFOLDED WRITING PADA SISWA KELAS V SDN 118/II CANDI - Ratih Juwita Novalia; Reni Guswita; Yelvia Prahagia (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
The problem of this research is that students have difficulty writing, students have difficulty in composing words in their own language and students are less developed in writing because of limited ideas, opinions and students' writing knowledge. When students are asked to write stories, students actually tell their ideas to their friends. This type of research is classroom action research (CAR). The data analysis technique of this research is qualitative data obtained from the results of teacher observation sheets and student observations, while quantitative data is learning outcomes obtained from learning outcomes tests. Based on the results of this study, it can be seen from the increase in the learning process with the percentage of teaching educators, namely cycle I meeting 1 66.66%, cycle I meeting 2 76.19% and cycle II meeting 1 85.7%, cycle II meeting 2 92, 30% and an increase in the learning process of students in cycle I meeting 1 53.84%, cycle I meeting 2 62.17% and cycle II meeting 1 73.07%, cycle II meeting 2 95.2% and the percentage of completeness of the number of students who achieved The KKM in the initial conditions was 36.3% or 8 students out of 22 students who achieved the KKM, in the first cycle the students who achieved the KKM were (54.5%) or (12) students from 22, and in the second cycle the students who achieved the KKM were ( 81.81%) or 18 of the 22 students. It can be concluded that the application of the Scaffolded writing model can improve the writing skill process of fifth grade students at SD Negeri 118/II Candi.